THE SEMIOTIC EXPLORING OF THE JAMBI MALAY CUCI KAMPUNG TRADITION - M. Ied Al Munir (PERADA, 2023)
There is a change in the cuci kampung tradition of the Jambi Malay community in Indonesia. This change is based on reinterpreting the sign attached to the tradition in question. This research is aimed at looking at this reinterpretation process. This research uses a descriptive-analytical qualitative method with a field and literature study as a background. Data was collected through interviews, observation, archiving and FGD. Apart from that, reading was also carried out on several related literatures. The collected data was analyzed using Charles Sanders Peirce's semiotic theory. This research produced several findings. First, the sign that is a reference in the cuci kampung tradition is the act of adultery which is sanctioned by stoning. Second, this sign is a reference for objects in the form of the cuci kampung tradition where the Jambi Malay community gave birth to this tradition with a traditional fine in the form of a goat or buffalo. Third, through reinterpreting the sign, the Jambi Malay community made changes to the cuci kampung tradition, both the procession and the traditional fines. The form of the procession became simpler, while the traditional fine changed into money